2020
DOI: 10.1111/1751-7915.13589
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of metal excess and superoxide, a highly toxic mixture in bacteria

Abstract: Heavy metal contamination is a serious environmental problem. Understanding the toxicity mechanisms may allow to lower concentration of metals in the metal-based antimicrobial treatments of crops, and reduce metal content in soil and groundwater. Here, we investigate the interplay between metal efflux systems and the superoxide dismutase (SOD) in the purple bacterium Rubrivivax gelatinosus and other bacteria through analysis of the impact of metal accumulation. Exposure of the Cd 2+-efflux mutant DcadA to Cd 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…Similar experiments were conducted using the ZntA mutant of E. coli to check the effect of Cd 2+ on SOD activity. Likewise, excess Cd 2+ in the medium resulted in an induced activity of the Mn‐Sod and decreased activity of the Fe‐Sod only in the ZntA mutant ( accompanying paper (Steunou et al , 2020b)). Altogether, these results showed that the accumulation of copper affected the expression and activity of superoxide dismutases presumably because of iron homoeostasis dysregulation linked to copper stress.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar experiments were conducted using the ZntA mutant of E. coli to check the effect of Cd 2+ on SOD activity. Likewise, excess Cd 2+ in the medium resulted in an induced activity of the Mn‐Sod and decreased activity of the Fe‐Sod only in the ZntA mutant ( accompanying paper (Steunou et al , 2020b)). Altogether, these results showed that the accumulation of copper affected the expression and activity of superoxide dismutases presumably because of iron homoeostasis dysregulation linked to copper stress.…”
Section: Resultsmentioning
confidence: 93%
“…The periplasmic copper protein CopI (Durand et al , 2015) is noteworthy induced under copper stress in R. gelatinosus and V. cholerae in response to Cu + . Cadmium stress in R. gelatinosus and V. cholerae also resulted in the induction of SodB in the CadA ATPase‐deficient mutants ( accompanying paper (Steunou et al , 2020b)).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…subtilis and other bacteria (Kihlken et al, 2008). As for copI, the copZ deletion in B. subtilis resulted in an increased sensitivity to both Cu + and Cd 2+ and expression of the copZA operon was induced in response to elevated concentrations of both metals (Moore et al, 2005;Steunou et al, 2020a). Similarly, in Pseudomonas (P.) aeruginosa Cu + induces the activation of the czcCBA operon involved in the efflux of Zn 2+ , Cd 2+ , and Co 2+ (Caille et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A band at about 22 kDa apparent molecular weight was also noticeably induced in the cadA mutant. This band corresponds to the cytosolic superoxide dismutase SodB (Steunou et al, 2020a). Similarly, in the cadR − mutant, CopI is also more induced compared to the wild-type FIGURE 7 | Expression level of HemN-H 6 in R. gelatinosus WT and HemN-H 6 strain in malate medium (-) or challenged with 1000 µM CdCl 2 (Cd 2+ ) or 500 µM CuSO 4 (Cu + ).…”
Section: Cadmium and Copper Cross-tolerance: Copi Is Involved In Cadmmentioning
confidence: 99%